2023
DOI: 10.3389/fphar.2023.1163160
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the role of obesity and lipids during tumor progression

Abstract: The dysregulation of the biochemical pathways in cancer promotes oncogenic transformations and metastatic potential. Recent studies have shed light on how obesity and altered lipid metabolism could be the driving force for tumor progression. Here, in this review, we focus on liver cancer and discuss how obesity and lipid-driven metabolic reprogramming affect tumor, immune, and stroma cells in the tumor microenvironment and, in turn, how alterations in these cells synergize to influence and contribute to tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 169 publications
0
1
0
Order By: Relevance
“…In addition, excess fatty acids (FAs) in the body can also stimulate ER stress, inducing hepatocellular damage, liver fibrosis and cirrhosis, and accelerating the development of hepatocellular carcinoma [ 84 ]. While combining conventional immune checkpoint inhibitors with mitochondrial fatty acid transporter inhibitors (e.g., etomoxir) can reverse the metabolic reprogramming of DC cells and restore the immune killing effect of T cells, which is an ideal medicine to target abnormal lipid metabolism [ 85 ]. Furthermore, it has been revealed that circ-DB is highly expressed in HCC patients with a high percentage of body fat and is associated with poor prognosis, suggesting that circ-DB may promote HCC progression through fatty acid synthesis (FAS), providing a new therapeutic target for targeting tumor lipid metabolism [ 86 ].…”
Section: Tumor-derived Exosomal Circrnas In Tumor Progressionmentioning
confidence: 99%
“…In addition, excess fatty acids (FAs) in the body can also stimulate ER stress, inducing hepatocellular damage, liver fibrosis and cirrhosis, and accelerating the development of hepatocellular carcinoma [ 84 ]. While combining conventional immune checkpoint inhibitors with mitochondrial fatty acid transporter inhibitors (e.g., etomoxir) can reverse the metabolic reprogramming of DC cells and restore the immune killing effect of T cells, which is an ideal medicine to target abnormal lipid metabolism [ 85 ]. Furthermore, it has been revealed that circ-DB is highly expressed in HCC patients with a high percentage of body fat and is associated with poor prognosis, suggesting that circ-DB may promote HCC progression through fatty acid synthesis (FAS), providing a new therapeutic target for targeting tumor lipid metabolism [ 86 ].…”
Section: Tumor-derived Exosomal Circrnas In Tumor Progressionmentioning
confidence: 99%